Disease Prediction By Articulatory Analysis Using Deep Learning. - RAMYA, S.; NANDHANA, S.; BHARKAVI, S. S. SHRI; SUGANYA, A.; THARANI, D. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
In today's technology, there is a lot of development involved in the field of medical. At the same time, the continuous monitoring of the patient's health condition also takes a vital role in the medical field. For example, the heart rate is to be simultaneously monitored. In this project, the continuous analysis of the heart beat is done by using the arduino microcontroller. In addition to this, the temperature is also monitored by using the LM35.The normal and abnormal heart rates are measured by connecting the pulse sensor to the patient. The overall process is continuously updated to required authority using GSM module and also updated in mobile application by using Bluetooth module. The emergency message to the doctor or relatives when the abnormal activity of pulse rate or temperature is detected. For that, the arduino IDE platform is employed. Hence an efficient health monitoring system can be designed.